The Transhumanism Handbook 2019
DOI: 10.1007/978-3-030-16920-6_56
|View full text |Cite
|
Sign up to set email alerts
|

Transhumanism in India: Past, Present and the Future

Abstract: Transhumanism is the philosophy or theory that hypothesizes that the human species can evolve beyond its present limited physical and mental capacities, especially with the help of science and technology. The Indian subcontinent has a particularly rich cultural heritage, which has a certain level of natural compatibility with the transhumanist core philosophies. From the pursuit of longevity to the morphological freedom exercised by the avatars of ancient polytheistic Gods and Goddesses, the legacy and heritag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hindus call these as Pushpaka Vimana, whence a thought about probability that these may have existed germinates in mind when one considers the description of distances travelled (in relatively short span of time as compared to the present) by various characters in epics like Ramayana or Mahabharata. However, these may constitute transhumanism (Ahamed et al, 2019), an aspect that is abundantly found in mythologies, epics and religious scriptures of all cultures irrespective of the geographic location.…”
Section: Dual Categoriesmentioning
confidence: 99%
“…Hindus call these as Pushpaka Vimana, whence a thought about probability that these may have existed germinates in mind when one considers the description of distances travelled (in relatively short span of time as compared to the present) by various characters in epics like Ramayana or Mahabharata. However, these may constitute transhumanism (Ahamed et al, 2019), an aspect that is abundantly found in mythologies, epics and religious scriptures of all cultures irrespective of the geographic location.…”
Section: Dual Categoriesmentioning
confidence: 99%
“…Urbanization began in the Indus plains in the Indian subcontinent around 2600 BC. The world's largest metropolises at that era were Harappa and Mohenjo-Daro, which rose to prominence around 2600 BCE (Ahamed et al, 2019). The Harappan folks consumed proteinrich, multigrain "laddoos" (edible balls) more than four thousand six hundred years ago (4600 years ago), according to a scientific investigation of the discovered material in the course of excavation in Rajasthan, which reveals the residents of Harappa practiced agriculture under favorable climatic circumstances.…”
Section: Historymentioning
confidence: 99%